Desert locust and its management in Nepal: a review - Shrestha, Suraj; Thakur, Gaurav; Gautam, Jayanti; Acharya, Namoona; Pandey, Meena; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Locusts are among the most dangerous agricultural pests. They are a group of short horned grasshoppers belonging to Acrididae family and are hemimetabolous insects. This group of grasshoppers have a unique character of changing habits and behaviors when they aggregate in a group and this habit is catalyzed by different environmental factors. In the adult stage, gregarious locusts migrate from one place to another in a swarm. Desert Locust, Schistocerca gregaria (Forksal), is one of those locusts which cause damage to different types of crop which fly in the direction of wind up to a distance of 150 km. Because of polyphagous feeding habits and swarming in a plague (large group of adults), this pest is considered as the hazardous migratory pest. These pests entered Nepal for the first time in 1962 and then in 1996. In 2020 the pest entered the country from India on three different dates 27th June and continued till 29th (5 districts), 12th July (1 district), and 16th July (2 districts). The swarms migrated to 53 districts and caused the considerable loss in agricultural and field crop in 1118 hectare. These pests are monitored on the basis of environmental factors and many tools and practices such as eLocust3, SMELLS (Soil Moisture for Desert Locust Early Survey), P-locust and SUPARCO Disaster Watch Desert Locust Situation Alert are being used. Their control is critical to food security. Many tools and techniques are integrated for prevention and management of these pests to minimize damage in the existing crops where they migrate. These are physical methods, cultural methods, use of botanicals, green muscle, PAN (phenylacetonitrile) and chemicals. Effective preventive management strategy relies on an improved knowledge of the pest biology, more efficient monitoring and control techniques.